A paradigm shift of quality Lac production in India - Jaiswal, AK; Roy, Sharmila; Sushil, SN (Indian Forester, 2020)
A study on lac production scenario in India was carried out for Chhattisgarh, Jharkhand, Madhya Pradesh, West Bengal, and the country as a whole. Lac production data have been analyzed plan period wise i.e. for Xth (2002-03 to 2006-07), XIth (2007-08 to 2011-12) and XIIth (2012-13 to 2016-17) plan. The perusal of data for India indicates rapid increase in kusmi lac production from 6175 tons in Xth plan to 7709 tons in XIth plan and 10,988 tons in XIIth plan per annum. The mean share of kusmi lac production of 27.92 per cent in Xth plan has increased to 47.44 per cent in XIth plan and 59.3 per cent in XIIth plan of the country. Considering Xth plan as base period, there was 69.9 per cent increase in share of kusmi lac during XIth plan and 112.4 per cent increase during XIIth plan period. The state wise shift in kusmi lac production was also witnessed. Highest shift was evident in Jharkhand followed by Chhattisgarh and West Bengal. This paradigm shift from rangeeni to kusmi lac may be due to changes in technological interventions to utilize ber trees for ensured availability of kusmi broodlac to growers.